Awareness of antibiotic use and antibiotic resistance amongst dental students - Tariq, Khaloud; Hassan , Muhammad; Wajahat , Mehreen; Muneer , Nadia; Imran , Eisha (Brazilian Dental Science, 2021)
Objective: Antibiotic resistance is one of the most threatening public health problems of 20th century. Along with physicians, dental practitioners also routinely prescribe medications for oral and dental infections. However, previous studies have shown that dental surgeons often prescribe antibiotics where new evidence have suggested other treatment measures. Since students in their clinical year prescribe antibiotics under supervision, it is important to understand if they are aware of severity of antibiotic resistance and its impact. Hence, the study aimed to assess awareness of antibiotic use and resistance amongst dental students. Material and Methods: Cross-sectional survey was conducted amongst 3rd and 4th year dental students of 4 colleges of Pakistan. A validated questionnaire was adopted from WHO and PHE (Public Health England). It included true or false and Likert scale questions relating to knowledge and attitude of antibiotic use and antibiotic resistance. Results: Out of 396 responses, majority students were not aware of the terms superbugs (69.7%) and AMR (79%). 89.6% thought that humans can become resistant to antibiotics. 88.6% agreed that antibiotic resistance is a major threat. 61.4% thought they couldn’t do much to stop antibiotic resistance. 87.6% agreed that doctors should only prescribe antibiotics when needed. Conclusion: Overall dental students were aware of antibiotic use and importance of antibiotic resistance although their knowledge associated with antibiotic resistance was not satisfactory. It is vital that students must be taught about mechanism of antibiotic resistance and good prescription practices.KeywordsAntibiotic resistance; Knowledge; Attitude; Dental students.